Long-Term Outcomes of the Minimally Invasive Ponto Surgery vs. Linear Incision Technique With Soft Tissue Preservation for Installation of Percutaneous Bone Conduction Devices - Strijbos, Ruben M.; Straatman, Louise V.; Calon, Tim G. A.; Johansson, Martin L.; de Bruijn, Arthur J. G.; van den Berge, Herbert; Wagenaar, Mariette; Eichhorn, Edwin; Janssen, Miranda; Jonhede, Sofia; van Tongeren, Joost; Holmberg, Marcus; et al. (Frontiers in Neurology, 2021)
Objective: A comparison of the surgical outcomes of the Minimally Invasive Ponto Surgery (MIPS) technique with the linear incision technique with soft-tissue preservation (LITT-P) for bone conduction devices after a follow-up of 22 months. Methods: In this multicentre randomised controlled trial, there was inclusion of sixty-four adult patients eligible for unilateral surgery. There was 1:1 randomization to the MIPS (test) or the LITT-P (control) group. Primary outcome was (adverse) soft tissue reaction. Secondary outcomes were pain, loss of sensibility, soft tissue height/overgrowth, skin sagging, implant loss, Implant Stability Quotient (ISQ) measurements, cosmetic scores and quality of life questionnaires. Results: Sixty-three subjects were analysed in the intention-to-treat population. No differences were found in the presence of (adverse) soft tissue reactions during complete follow-up. Also, there were no differences in pain, wound dehiscence, skin level, soft tissue overgrowth and overall quality of life. Loss of sensibility (until three months post-surgery), cosmetic scores and skin sagging outcomes were better in the MIPS group. The ISQ was higher after the LITT-P for different abutment lengths at various points of follow-up. Implant extrusion was non-significantly higher after the MIPS (15.2 %) compared to LITT-P (3.3 %). Conclusion: The long-term results show favourable outcomes for both techniques. The MIPS is a promising technique with some benefits over the LITT-P. Concerns regarding non-significantly higher implant loss may be overcome with future developments and research.